Electrolyte disorders in community subjects: prevalence and risk factors - Liamis, George; Rodenburg, Eline M; Hofman, Albert; Zietse, Robert; Stricker, Bruno H; Hoorn, Ewout J (The American journal of medicine, 2013)
Electrolyte disorders have been studied mainly in hospitalized patients, whereas data in the general population are limited. The aim of this study was to determine the prevalence and risk factors of common electrolyte disorders in older subjects recruited from the general population. A total of 5179 subjects aged 55 years or more were included from the population-based Rotterdam Study. We focused on hyponatremia, hypernatremia, hypokalemia, hyperkalemia, and hypomagnesemia. Multivariable logistic regression was used to study potential associations with renal function, comorbidity, and medication. The adjusted mortality also was determined for each electrolyte disorder. A total of 776 subjects (15.0%) had at least 1 electrolyte disorder, with hyponatremia (7.7%) and hypernatremia (3.4%) being most common. Diabetes mellitus was identified as an independent risk factor for hyponatremia and hypomagnesemia, whereas hypertension was associated with hypokalemia. Diuretics were independently associated with several electrolyte disorders: thiazide diuretics (hyponatremia, hypokalemia, hypomagnesemia), loop diuretics (hypernatremia, hypokalemia), and potassium-sparing diuretics (hyponatremia). The use of benzodiazepines also was associated with hyponatremia. Hyponatremic subjects who used both thiazides and benzodiazepines had a 3 mmol/L lower serum sodium concentration than subjects using 1 or none of these drugs (P < .001). Hyponatremia and hypomagnesemia were independently associated with an increased mortality risk. Electrolyte disorders are common among older community subjects and mainly associated with diabetes mellitus and diuretics. Subjects who used both thiazides and benzodiazepines had a more severe degree of hyponatremia. Because even mild electrolyte disorders were associated with mortality, monitoring of electrolytes and discontinuation of offending drugs may improve outcomes.